Electrosurgery and 5% Imiquimod Cream as a Combination Therapy for Perianal Condyloma Acuminata in a HIV Patient - Setyowatie, Lita; Faradila, Anandita (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Condyloma acuminata (CA) is a common sexually transmitted infection caused by the human Papillomavirus (HPV) infection. It is characterized by single or multiple lesions in the anogenital area accompanied by itching, discharge, or bleeding. CA in HIV (human immunodeficiency virus) - positive patients can experience a low response to various therapeutic modalities, which may lead to consideration of choosing combination therapy to increase the effectiveness of therapy. Case: We report a case in a twenty-one-year old male with multiple warts on the perianal area. Within four months, the warts had covered the perianal area, with hemorrhoids emerging as complications. The patient had trichloroacetic acid treatment three times but did not respond. The patient is male who have sex with male, and there has been a history of multisexual partners. The diagnosis was made by clinical and histopathological examinations. The patient is HIV-positive and has been receiving antiretrovirals regularly. He got a combination therapy of electrosurgery and 5% imiquimod cream for 9 weeks and showed excellent results. Discussion: Standard topical medication is an effective treatment for condyloma acuminata, but infiltrative and recurrent lesions often require ablative and surgical treatment. Conclusion: Electrosurgery in combination with imiquimod proved to be effective and shortening the treatment regimen in the treatment of perianal CA.